Imperfect public goods and the logic of selective exit in EU interest organisations. Issue 5 (3rd September 2017) - Eising, Rainer
Abstract: How do national members react to performance failures of EU-level interest groups? Albert Hirschman suggested two responses: exit and voice. Building on this distinction, the article develops the category of selective exit which denotes members' interest representation outside the boundaries of the EU-level interest organisation in response to performance failures. Selective exit enables members to raise voice from within and exert pressure from outside the group. The empirical test of this proposition draws on 100 interviews with national interest groups which provide evidence on the lobbying performance of EU-level groups on 20 EU directive proposals. Exact logistic regressions analyse their responses to the quality of information supply by the EU-level group and the congruence of their preferences with the EU-level group's common position. The findings demonstrate that members join coalitions and participate in media debates to counter perceived performance failures. The conclusion summarises the findings and points out avenues for further research.